2017 Transport Sector : Private Participation in Infrastructure - World Bank Group (World Bank, Washington, DC, 2018)
Transport PPI investments form an integral part of total PPI investments. Since 2008, transport PPI investments have been forming a larger and larger percentage of PPI investments across the four sectors (energy, ICT, water and transport). PPI investments in transport used to attract 23 to 29 percent of all PPI investments prior to 2011. After 2011, transport PPI investments haveconsistently garnered more than 30 percent of all PPI investments, reaching a high of 61 percent i